Cognitive consequences of COVID-19: results of a cohort study from South America - Lucía Crivelli; Ismael Calandri; Nicolás Corvalán; María Agostina Carello; Greta Keller; Carlos Martínez; Micaela Arruabarrena; Ricardo Allegri (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Neurological and psychiatric manifestations associated with SARS-CoV-2 infection have been reported throughout the scientific literature. However, studies on post-COVID cognitive impairment in people with no previous cognitive complaint are scarce. Objective: We aim to investigate the impact of COVID-19 on cognitive functions in adults without cognitive complaints before infection and to study cognitive dysfunction according to disease severity and cognitive risk factors. Methods: Forty-five post-COVID-19 patients and forty-five controls underwent extensive neuropsychological evaluation, which assessed cognitive domains such as memory, language, attention, executive functions, and visuospatial skills, including psychiatric symptomatology scales. Data were collected on the severity of infection, premorbid medical conditions, and functionality for activities of daily living before and after COVID-19. Results: Significant differences between groups were found in cognitive composites of memory (p=0.016, Cohen’s d= 0.73), attention (p<0.001, Cohen’s d=1.2), executive functions (p<0.001, Cohen’s d=1.4), and language (p=0.002, Cohen’s d=0.87). The change from premorbid to post-infection functioning was significantly different between severity groups (WHODAS, p=0.037). Self-reported anxiety was associated with the presence of cognitive dysfunction in COVID-19 subjects (p=0.043). Conclusion: Our results suggest that the presence of cognitive symptoms in post-COVID-19 patients may persist for months after disease remission and argue for the inclusion of cognitive assessment as a protocolized stage of the post-COVID examination. Screening measures may not be sufficient to detect cognitive dysfunction in post-COVID-19 patients.